The Influence Of e-Samsat-Based Tax Administration Modernization of Motor Vehicle Tazpayer Compiliance (Empirical Study of Samsat Sumedang Regency) - Heldiana, Mela; Yuniawati, Ayi Srie (SINTESA, 2024)
This study aims to find out how the modernization of e-SAMSAT-based tax administration in Sumedang Regency's SAMSAT, to find out how the compliance of Motor Vehicle Taxpayers in Sumedang Regency's SAMSAT, and to find out how the effect of modernization of e-SAMSAT-based tax administration on Motor Vehicle Taxpayer compliance in SAMSAT Sumedang Regency. The results of the data analysis show that modernization of e-SAMSAT-based tax administration is in the very good category or 84.7% because the implementation of modernization of e-SAMSAT-based tax administration is as expected. The results of data analysis also show that the compliance of Motor Vehicle Taxpayers is in the very good category or 87.8% to find out the amount of contribution made by the modernization of e-SAMSAT-based tax administration to the compliance of Motor Vehicle Taxpayers by 69.5%. Furthermore, the results of hypothesis testing show that ????ℎ???????????????????? is 14.851 and ???????????????????????? is 1.983. Thus the result is ????0 rejected and ????a accepted. Therefore, there is an influence between the modernization of e-SAMSAT-based tax administration and the compliance of Motor Vehicle Taxpayers at the SAMSAT office in Sumedang Regency.